Serum free light-chain concentration and relationship with some characteristics of patients with multiple myeloma - Van Nguyen-Thanh Phan; Loc Thi Cao; Minh Duc Tong; Trung Hoang Nguyen; Kha Van Tran; Dung Trong Le (Revista Cubana de Medicina Militar)
Introduction: Quantifying serum free light-chain is a valuable test to determine the risk at the time of diagnosis, assess the response to treatment, and monitor the recurrence of multiple myeloma. Objective: To investigate the characteristics of serum free light-chain concentration and its relationship with some clinical and subclinical characteristics in patients with multiple myeloma. Methods: Descriptive, retrospective, non-controlled study was conducted, in 74 patients with multiple myeloma. All patients were completed with quantitative tests serum free light-chain κ, and serum free light-chain λ. Results: Intact immunoglobulin multiple myeloma accounted for most patients (81%). Most patients had abnormal serum free light-chain at the time of diagnosis (98.6%). High serum free light-chain concentration was correlated with M protein concentration > 3 g/dL (p< 0.05) and there was no statistically significant correlation between high serum free light-chain and other clinical and subclinical features. Conclusion: Most patients with multiple myeloma have an elevated serum free light-chain at admission time. Correlation of high serum free light-chain with increased serum M protein was noted.